Al’âb Lughawiyyah Fî Ta’lîmi Al-‘Arabiyyah Litanmiyati Mahârah Al-Kalâm Ladâ At-Thulâb Fî Sdit Ar-Raayah - Amalia Nur Sania Rachmah (Mauriduna: Journal of Islamic Studies, 2020)
تهدف هذه الدراسة إلى معرفة الألعاب اللغوية في تعليم اللغة العربية لتنمية مهارة الكلام، وليس جميع الألعاب مناسبة استخدامها فيه، فحاولت الباحثة البحث عن بعض الألعاب المناسبة. واللغة العربية هي إحدى موضوعات دراسية اللغة الأجنبية التي درست في كثير من المدارس الإسلامية، منها المدرسة الابتدائية الإسلامية التابعة لمؤسسة الراية. وفي عملية تعليم وتعلم اللغة العربية ليست سهلة خاصة في تنمية مهارة الكلام التي تشمل قدرة المتعلمين على التعبير أو وصف شيء ما من خلال الكلمات، وقدرة المتعلمين على التواصل اللفظي باستخدام المفردات العربية التي تمت دراستها. والصعوبة المواجة هي أن اللغة العربية ليست اللغة المستخدمة في المحادثة اليومية، وقلة تطبيقها خارج ساعات الدوام المدرسي. وفي هذه الدراسة، استخدمت الباحثة منهجًا وصفيًا وتجريبيًا بتطبيق سبع أنواع من الألعاب اللغوية لخمسة عشر دارسا من الصف الثاني في المدرسة الإسلامية التابعة لمؤسسة الراية. وأظهرت نتائج تطبيق الألعاب اللغوية من حيث ​​نسبة الدرجة المتوسطة أن 81.6٪ من المتعلمين راغبين في تعلم اللغة العربية باستخدام الألعاب اللغوية، و 18.4٪ من المتعلمين لم يعجبهم ذلك. والختام، فإن استخدام الألعاب اللغوية في عملية تعليم اللغة العربية تؤثر المتعلمون في استيعاب الدروس بشكل جيد. This study aimed to show language games that are suitable in Arabic teaching especially to develop student’ speaking skills, because not all games are suitable for use in it, so the researcher looked for some suitable games to use. Arabic is one of the subjects of foreign language studies that have been studied in many Islamic schools, including the Ar-Raayah Foundation Islamic Primary School (SDIT Ar-Raayah). In the process of teaching and learning of Arabic language is not too easy, especially in developing speaking skills, which include the ability of students to express or describe things through words, and the ability of students to communicate verbally using Arabic vocabulary that is learned. The difficulty is that Arabic is not the language used in daily conversation, and the lack of its application outside school hours. In this study,the researcher used a descriptive and experimental approach by applying seven kinds of language games to fifteen second grade students at SDIT Ar-Raayah. The results of applying language games in terms of the average level showed that 81.6% of students liked how to learn Arabic using language games, and 18.4% of students did not like it. In conclusion, the use of language games in the Arabic teaching process gave good affects to students in understanding the lesson.